ENHANCEMENT OF DISSOLUTION RATE OF MODAFINIL USING SOLID DISPERSIONS WITH POLYETHYLENEGLYCOLS - Vyas Jigar; Patel Jayvadan; Jain D. A. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Solid dispersions (SDs) of modafinil (MDF) were prepared using polyethyleneglycols (PEGs), in 1;1, 1;2 and 1;4 proportions by fusion, solvent evaporation and physical mixing method. Differential scanning calorimetry (DSC) and X-ray powder diffractometry (XRD) were used to examine the physical state of the drug. The data from the XRD showed that the drug was converted to amorphous form as the number and intensity of peaks were decreased in solid dispersion as compared to pure drug and physical mixture of drug and carrier. DSC thermograms also confirmed the change in physical state of the drug as the peaks were altered or disappeared. With the highest ratio of the carriers (1:4), the drug solubility was enhanced by 38.68, 34.78 and 9.29 folds in solvent evaporation, fusion and physical mixing methods respectively. Solid dispersion batch S6 containing drug:PEG6000 in 1:4, was selected to be formulated as tablet (batch TS6) and evaluated for in vitro drug dissolution & six month stability. An increased dissolution rate of modafinil was observed from SDs and PMs, as compared to pure crystalline drug. The dissolution rate of modafinil from its PMs or SDs increased with an increasing amount of polymer.Key words: Fusion, solvent evaporation, physical mixture, in vitro dissolution, characterization.